EUTHANASIA AND ASSISTED SUICIDE: AN ANALYSIS FROM RICOEUR'S CONCEPTION OF AUTONOMY AND VULNERABILITY (Isagoge - Journal of Humanities and Social Sciences, 2022)
The research aims to analyze the concepts of autonomy and vulnerability, intending to reinterpret them so that they serve as a basis for the central discussion that orbits around the issue of euthanasia and assisted suicide. The concept of autonomy is worked on in an analytical perspective, developing in stages that allow its conceptual apprehension, as well as the antagonistic concept of vulnerability. The paradoxical relationship of the theme characterizes human vicissitudes, exposing its limits and weaknesses when faced with the need for authorization of the patient who wants assisted death. The intended analysis of the concepts is fundamental to anchor the debate about the acts of consent that authorize questionable medical procedures, and, touching on the central theme, it serves as a point of reflection to discuss whether there is a reformulation of the concept of human dignity that are applied to the elderly, psychiatric patients, and children. The following work has the general objective of understanding the ethical-medical limit about the end of human life, and how such a limit is submitted to the judgment of value that every human life has. This objective is combined with the analysis of individual autonomy, with a view to understanding how the concept must be exercised in order not to confront the most essential aspects of life, as well as the specific objective of analyzing the influence of heteronomy concepts in cases of euthanasia.
Keywords: Autonomy; Vulnerability; Dignity; Life; Euthanasia; Consent